3D Statistical Head Modeling for Face/head-Related Product Design: A State-of-the-Art Review. (June 2023) - Zhang, Jie; Luximon, Yan; Shah, Parth; Li, Ping
Abstract: In the field of face/head-related product design, 3D statistical models (3DSMs) of human heads and faces are widely used to model geometric variations, generate representative models and reconstruct head geometries of a target population. They therefore have many applications to face/head-related products, including ergonomic product design, sizing system establishment, fit assessment, individual product customization, and virtual try-on. Numerous studies have created 3DSMs for various populations and further applied them in the design of various products. This paper conducts a state-of-the-art review of 3DSMs of human heads and faces for facewear/headwear design. It focuses on different essential processes in the modeling pipeline, including 3D head data capture techniques and instruments, 3D head scan datasets, statistical modeling pipelines (particularly facial mesh alignment, facial landmark detection and facial shape correspondence), and product application scenarios. Finally, the paper explicitly highlights unsolved challenges and proposes the potential directions for future research. The paper provides an overview of 3D statistical head modeling and its applications, and will hopefully help inspire researchers to solve the existing challenges and promote ergonomic design development. Highlights: We conducted a detailed state-of-the-art review on consturcting and applying 3D statistical head models for product design. We discussed method comparisons, research limitations and future work for 3D statistical head modeling. We help inspire researchers to solve the existing challenges and promote ergonomic headwer design development.